التكتلات الاقتصادية وتعزيز فرص التسويق الدولي للمنتجات الزراعية الجزائرية - محيريق, فوزي; هزلة, نجلاء; حيمر, زينب (University of Eloued جامعة الوادي, 2019)
تهدف دراستنا إلى معرفة أثر الانضمام للتكتلات الاقتصادية على الصادرات الزراعية للجزائر، لما لها من تأثير في خلق فرص تسويقية دولية متنوعة ومتعددة وذلك من خلال استراتيجيات اقتحام الأسواق الدولية وأهمها التصدير، ولتحقيق هذه الدراسة تم تحليل اتجاه تطور الصادرات الزراعية الجزائرية قبل وبعد دخول الجزائر في كل من الاتفاقيات الإقليمية والدولية التالية: إتحاد المغرب العربي، منطقة التجارة الحرة العربية الكبرى والشراكة الأورو متوسطية خلال الفترة (2016-1989)، وأظهرت الدراسة إن إنضمام الجزائر إلى التكتلات الاقتصادية أدى إلى تعزيز فرص التسويق الدولي لمنتجاتها الزراعية والمتمثلة في زيادة حجم الصادرات الزراعية الجزائرية وذلك من خلال إتساع حجم السوق وتحقيق وفورات الحجم وزيادة الإنتاجية وتحسين القدرة التنافسية الدولية للبلد من حيث السعر والجودة وتقسيم العمل بين الدول المتكاملة وتفعيل مبدأ التخصص في إنتاج السلع التي تتمتع فيها كل دولة بمزايا نسبية وتنافسية. Abstract: Our study aims to find out the impact of joining the economic blocs on the agricultural exports of Algeria, because of its impact in creating a variety of international marketing opportunities through a variety of strategies to penetrate the international markets, most important of which are exports. Among the following regional and international agreements: the Arab Maghreb Union, the Greater Arab Free Trade Area and the Euro-Mediterranean Partnership during the period (2016-1989), the study showed that Algeria's accession to the economic blocs led to the promotion of international marketing opportunities for products. It aims at increasing the volume of Algerian agricultural exports through expanding the market size, achieving economies of scale, increasing productivity, improving the international competitiveness of the country in terms of price, quality, division of labor among integrated countries and activating the principle of specialization in the production of goods in which each country enjoys comparative and competitive advantages.
Economic blocs and promotion of international marketing opportunities for Algerian agricultural products
الملتقى الدولي الثامن حول: الاتجاهات الحديثة للتجارة الدولية وتحديات التنمية المستدامة نحو رؤى مستقبلية واعدة للدول النامية 02/ 03 ديسمبر 2019 - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - جامعة الشهيد حمه لخضر - الوادي
Keywords: تكتلات اقتصادية؛ تسويق دولي؛ صادرات زراعية. تصنيف JEL : F15؛ M31؛ F1; Economic blocs; International marketing; Agricultural exports. Jel Classification Codes : F15؛ M31 ؛F1